The reflection of Edward Hopper’s work in the films L’Eclisse, Strangers on a Train y Manchester by the Sea - Mendieta Rodríguez, Elios (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2018)
Many films have been influenced, in a direct or indirect way, by Edward Hopper’s pictorial work. This article studies the dialogue between cinema and painting with the pictures of the North American artist as a base. For this analysis we choose films which, in a different way, there are echoes of Hopper’s art. These films are L’Eclisse (1962), by Michelangelo Antonioni; Strangers on a Train (1951), by Alfred Hitchcock, and Manchester by the Sea (2016), by Kenneth Lonergan.